Analisis ciri dan fungsi mantra pengobatan pada tuturan belian bawo di barong tongkok - Kiki Indah Royani; Syaiful Arifin; Nina Queena Hadi Putri (Universitas Ahmad Dahlan, 2020)
The problems examined in this study are (i) What are the characteristics of the Belian Bawo Dayak Benuaq treatment in the Barong Tongkok District, West Kutai Regency, East Kalimantan Province; (ii) What is the function of the Belian Bawo Dayak Benuaq tribal medicine in the Barong Tongkok District, West Kutai Regency, East Kalimantan Province. The objectives of this study are (i) To describe the characteristics of the Dayak Benuaq Belian Bawo treatment spells in Barong Tongkok District, West Kutai Regency, East Kalimantan Province; (ii) Describe the function of the Dayian Benuaq Belian Bawo Belian treatment spells in Barong Tongkok District, West Kutai Regency, East Kalimantan Province. The method used in this study is an analytical method using observation techniques, structured interviews, notes, records and listening. The results obtained from the analysis of data that has been done by the author, it was found that Biano Belian utterances in the form of (i) Mantra consists of several series of words that have elements of rhythm and rhyme; (ii) Are oral, magical or magical; (iii) Asoferik (special language between speaker and interlocutor); (iv) Many words that are less commonly used in daily life. The function of the Dayak continent medicine mantras is based on the analysis of its functions, namely (i) The function of the mantra as a social control tool (advice); (ii) The function of the mantra as a reminder (warning); (iii) The function of the mantra as tolerance; (iv) The function of the mantra as a means of prayer.